2016
DOI: 10.1016/j.mjafi.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health education intervention on food safety and hygiene of street vendors: A pilot study

Abstract: The street vendors do not meet required standards given by BIS for food safety. Health education alone can only partly improve food safety practices of street vendors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 3 publications
0
27
0
1
Order By: Relevance
“…Some studies find statistically significant-yet still minor, partial, or time-bound changes in behavior-demonstrating the limitations of training. Singh et al 2016, in a study of street food vendors in India, showed that training resulted in only partial behavior change, but was not enough for vendors to meet standards. Acikel et al (2008), in a study of hospital food workers in Turkey, found that wearing jewelry and watches declined after training (self-reported), but that other hygienic behavior remained the same, as did the level of enteric colonies growing on the hands of participants after training.…”
Section: Factors That Motivate Food Safety Capacity and Behavioral Chmentioning
confidence: 99%
“…Some studies find statistically significant-yet still minor, partial, or time-bound changes in behavior-demonstrating the limitations of training. Singh et al 2016, in a study of street food vendors in India, showed that training resulted in only partial behavior change, but was not enough for vendors to meet standards. Acikel et al (2008), in a study of hospital food workers in Turkey, found that wearing jewelry and watches declined after training (self-reported), but that other hygienic behavior remained the same, as did the level of enteric colonies growing on the hands of participants after training.…”
Section: Factors That Motivate Food Safety Capacity and Behavioral Chmentioning
confidence: 99%
“…To achieve all these, it is necessarily to involve all the stakeholders in the street food vending business, such as the street vendors, consumers, national and local governments, and civil societies. Public education is another aspect that can be applied in trying to reduce the risk from street food [ 50 ]. For all the stakeholders involved, awareness of the dangers posed by unhygienic handling of street food can be disseminated to them through the mass media.…”
Section: Resultsmentioning
confidence: 99%
“…Regularised food inspection should be conducted by Health Inspectors to determine compliance [18], with the law and gather evidence for enforcement in cases of noncompliance. Evidence states that the impact of health education intervention [19], on food safety and hygiene [20] and implementing a skill development program [21], in street vendors can prevent traveler's diarrhoea [22] and other food borne illnesses.…”
Section: Discussionmentioning
confidence: 99%